“AVESTO” and KARAKALPAK FOLK DASTAN “SHARIYAR” (The source of education, traditions and heritage, continuity and relationship problems) - Allambergenov, E.K. (FAN va JAMIYAT, 2020)
The article is devoted to the description uf the content of such parts as «Yasna», «Vandidat», "Yashta», «Visparadi», "Vendidot» of the holy book Avesto that teaches people to differ good from bad arid to protect their rights. There have been analysed such notions as morality, good and evil, rights. Violation of rights, civilian rights, family rights and law education. The author enemies to the conclusion that «Avesto» is not only of a national but of general human value as well.